Anaerobic codigestion of excess sludge with chicken manure with a focus on methane yield and digestate dewaterability. (September 2022) - Wang, Tianfeng; Xing, Zhijie; Zeng, Liyuan; Peng, Cheng; Shi, Hailong; Cheng, Jay J.; Zhang, Qingfang
Abstract: The effects of the mixing ratio of excess sludge (ES) with chicken manure (CM) on methane yield and digestate dewaterability were investigated at thermophilic and mesophilic temperatures. Batch experiments were performed at five different volatile solid ratios (ES/CM). Compared with anaerobic digestion of ES alone, codigestion of ES with CM increased methane yield 82.4–123.1 mL g −1 -VSadded (mesophilic) and 33.9–171.3 mL g −1 -VSadded (thermophilic), respectively. The normalized capillary suction time (NCST) and TS of thickened digestate (3.09–8.29 s g −1 -TS, 17.51 %–18.83 %) at mesophilic temperatures were superior to these (6.81–10.14 s g −1 -TS, 16.66 %–18.30 %) at thermophilic temperatures. But the gap decreased with increasing CM proportion in the substrate. The results indicated that anaerobic codigestion of ES and CM at a proper mixing ratio (ES/CM = 1:1.5–2) could obtain a high methane yield and an adequate digestate dewaterability. Graphical abstract: Unlabelled Image Highlights: Codigestion improves methane yield 33.9–171.3 g −1 -VS at thermophilic temperature. Codigestion improves methane yield 82.4–123.1 g −1 -VS at mesophilic temperature. Microbial communities are more sensitive to temperature than substrate. NCST and TS of thickened digestate increased with the increasing of initial TS.